2018
DOI: 10.1016/j.fuel.2017.10.065
|View full text |Cite
|
Sign up to set email alerts
|

CLOU process performance with a Cu-Mn oxygen carrier in the combustion of different types of coal with CO2 capture

Abstract: The Chemical Looping with Oxygen Uncoupling (CLOU) process is a Chemical Looping Combustion (CLC) technology that allows the combustion of solid fuels with inherent CO2 separation by using oxygen carriers based on metal oxides. This technology has low energy penalty and thus low CO2 capture costs. In CLOU, the oxygen carrier must be able to release gaseous oxygen which limit the availability of metal oxides for this process. In this work, the suitability of oxygen carrier particles containing 34 wt.% CuO and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…On evaluation of the operating conditions set for these tests, the different oxygen carrier to fuel ratio used is worthy of note. It has recently been suggested that a low oxygen carrier to fuel ratio, which is related to high variation in oxygen carrier conversion during redox cycles in a CLC unit, damages the mechanical integrity of the particles [42]. This is in agreement with the decrease in the mechanical strength of the particles in the experiments with coal, where the oxygen carrier to fuel ratio was  = 1-1.5.…”
Section: Characterization Of the Particles Used In Continuous Testssupporting
confidence: 77%
See 1 more Smart Citation
“…On evaluation of the operating conditions set for these tests, the different oxygen carrier to fuel ratio used is worthy of note. It has recently been suggested that a low oxygen carrier to fuel ratio, which is related to high variation in oxygen carrier conversion during redox cycles in a CLC unit, damages the mechanical integrity of the particles [42]. This is in agreement with the decrease in the mechanical strength of the particles in the experiments with coal, where the oxygen carrier to fuel ratio was  = 1-1.5.…”
Section: Characterization Of the Particles Used In Continuous Testssupporting
confidence: 77%
“…In this sense, Pérez-Vega et al [38] after 45 h of operation. This oxygen carrier showed excellent performance in a CLOU unit burning coal, while the evolution of its mechanical properties depended on the solids circulation rate [42]. Thus, particles maintained high mechanical strength when the solids circulation rate was high enough to support an oxygen carrier to fuel ratio higher than 3-4.…”
Section: Similar Differences In Performance Between Both Types Of Chementioning
confidence: 97%
“…Furthermore, an oxygen carrier consisting of CuO, Fe 2 O 3 , and MgAl 2 O 4 has been explored for chemical looping combustion applications [134]. Adanez-Rubio et al [135] discussed the applicability of CuO/Mn 3 O 4 as an oxygen carrier for chemical looping. The lifetime of this oxygen carrier was found to be significant for a large oxygen carrier/fuel ratio.…”
Section: Engineering Of Oxygen Carriersmentioning
confidence: 99%
“…The oxygen carrier must have adequate oxygen equilibrium partial pressure at temperatures of interest for combustion (800-1200ºC) and also withstands long periods of continuous redox cycles. Up to date, only few materials have demonstrated their adequacy for the CLOU process [10][11][12], mostly based on copper oxides or perovskites. Thus, they are also expensive oxygen carriers when compared to those for iG-CLC.…”
Section: Introductionmentioning
confidence: 99%